The Potential Of Alkanolamide As A New Additive In Natural And Synthetic Rubber Compounds - Surya, Indra (2016)
The potential of Alkanolamide (ALK) as a new additive in natural and synthetic rubber compounds was studied. The ALK was prepared by reacting Refined Bleached Deodorized Palm Stearin (RBDPS) with diethanolamine. The unfilled Natural Rubber (NR) and Polychloroprene Rubber (CR) compounds, silica-filled NR compound, and Carbon Black (CB) filled NR, Epoxidised Natural Rubber (ENR-25) and Styrene-Butadiene Rubber (SBR) compounds were carried out. In this study, various loading of ALK was incorporated into the rubber compounds which were vulcanised with sulphur accelerated vulcanization system. The main objective is to investigate the effect of ALK loading on properties of the different types of rubber compounds. It was found that ALK could be utilised not only as a curative additive but also as an internal plasticiser in the rubber compounds. The ALK has improved the cure characteristics of the rubber compounds where the increased in cure rates and torque differences were observed. The scorch and cure times of unfilled and silica-filled NR, CB-filled NR, ENR-25 and SBR compounds were shortened as the increased of ALK loadings. The torque difference was increased up to a certain optimum ALK loading of each type of rubber compounds. The ALK also exhibited higher tensile modulus, tensile strength, hardness, resilience and crosslink density, especially up to certain optimum loadings of ALK; 0.6 and 5.0 phr for unfilled and silica-filled NR compounds, respectively; 5.0 phr for CB-filled NR and SBR compounds, and 1.0 phr for CB-filled ENR-25 compound. Study on reinforcement effects of CB and silica on the rubbers showed that the higher mechanical properties of silica-filled NR compound, and CB-filled NR, ENR-25, SBR compounds were achieved. These were attributed from a better dispersion and stronger rubber – filler interaction as well as the cure enhancement phenomenon due to the functions of ALK as a plasticiser and accelerator in the filled rubber compounds. The infrared spectroscopic study on unfilled CR and silica-filled NR vulcanisates proved that ALK has an ability to form crosslinks with CR molecules through the formation of C−O chemical bonds; and the formation of O−N−O coupling bonds proved that ALK has interacted chemically with the silica. The morphology study on the rubber vulcanisates with and without ALK proved that Scanning Electron Microscopy (SEM) micrographs of silica-filled and CB-filled NR compounds, CB-filled ENR-25 and SBR compounds with ALK exhibited a greater matrix tearing line and surface roughness due to better filler dispersion and stronger rubber – filler interaction. The higher elongations at break and lower torques minimum of the vulcanisates of filled and unfilled NR, CB-filled ENR-25 and SBR compounds as the loadings of ALK were increased together with the better filler dispersion proved the function of ALK as an internal plasticiser.